(untitled) (Journal of Bangladesh Academy of Sciences, 2017)
Measurement of uptake by using the image based bio-distribution of 99mTc-DMSA (Dimercapto succinic acid) and 99mTc-DTPA (Diethylene triaminepenta acetic acid) in Kidney, Spleen and Liver with frame to frame analysis has been evidenced as the simplified way than the existing computer program based methodology, like MIRD and others. In this study, 100 patients were included in each scan. For 99mTc-DTPA scan, the mean uptake percentage for Kidney was 84.06% and that for Spleen was 7.80% and for Liver was 8.13% in which 66 patients were male and 34 were female age ranging from 3 (three) months to 70 (seventy) years. On the other hand,99mTc-DMSA scan was executed for 60 (sixty) male and 40 (forty) female patients; the mean values of uptake percentage for Kidney, Spleen and Liver were 87.40%, 5.99% and6.60% respectively. It was manifested that the uptake percentages of radiopharmaceuticals were the highest in kidney for youngers whereas those values in other organs were lower than adults. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 105-114, 2017